Rebranding Wisata Giwangkara River Tubing Neglasari sebagai Upaya Pembangunan Pedesaan - A.Nur Fajar Oktaviani; Risky Amelia Putri; Saidati Arifa Ilma; Hidayat Nur Alim; Nurul Amirah; Zessy Ardinal Barlan (Jurnal Pusat Inovasi Masyarakat, 2024)
The tourism sector plays an important role in supporting rural development through the establishment of tourism villages, but not all tourist attractions are successful in creating effective branding. This action research activity aims to make efforts to rebrand Giwangkara River Tubing Tour in Neglasari Village as a strategic step in rural development. The method used was a descriptive qualitative approach, obtained from in-depth interviews with tour managers. The results showed that Giwangkara River Tubing Tourism has not done optimal branding due to the lack of human resources in managing social media accounts and the lack of skills in graphic design affects the effectiveness of social media management. The existence of rebranding efforts has a positive impact as seen from the increase in the number of followers, viewers, and likes on @giwangkararivertubing Instagram reels. In addition, the number of tourist visitors also increased after the implementation of the rebranding action. This activity emphasizes the importance of a good branding strategy in increasing tourism attractiveness and supporting rural development. Rebranding not only increases online visibility but also encourages local economic growth through increased tourist visits. The results of the implementation of this activity are expected to be a reference for other tourism managers in developing effective and sustainable branding strategies. Rebranding efforts that involve digital skills training for tourism managers are also recommended to ensure sustainability and long-term success.